Prevalence, Causes, and Impacts of Pornography Consumption Among Adolescents in Wamakko Local Government Area, Sokoto State, Nigeria - Kamal Muhammad Sani; Maryam Mamman Adam; Fatima Mohammed; Madina Sani Udu; Ineke Joseph Iko-Ojo; Ahmed Haruna Danjuma; Kamal Kaila Umar (PT Mattawang Mediatama Solution, 2024)
This paper aims to study the prevalence, causes, and impacts of pornography consumption (PC) among adolescents in Wamakko Local Government Area (WLGA), Sokoto State, Nigeria. A mixed-methods approach was used to gather data for this study. A randomized sampling technique was used to select a total of 550 respondents from the 11 political wards in WLGA, comprising 330 males and 220 females. Microsoft Word and Excel (2016 version) were used for data entry, editing, and cleaning. Furthermore, Statistical Package for the Social Sciences (SPSS Version 20) software was used to analyze the quantitative data. The results show that 63.3% of the sampled respondents reported being exposed to pornographic content on the internet, primarily through websites and social media platforms. Additionally, the study found that factors like peer influence, the lack of comprehensive sex education, and adolescents’ natural curiosity contribute to adolescent engagement in PC. In conclusion, the study recommends implementing comprehensive sex education in schools, promoting open communication between parents and their children, and raising awareness about the potential consequences of PC.